Nosná ŽB konstrukce objektu hotelu - Macourková, Klára (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Diplomová práce se zabývá statickým řešením monolitické železobetonové konstrukce objektu hotelu. Předmětem řešení je návrh železobetonové monolitické bodově podepřené stropní desky, sloupů, základových patek, základových pasů a schodiště. Posouzení těchto konstrukcí je provedeno pomocí I. mezního stavu únosnosti.

The thesis deals with the static solution of monolitic reinforced concrete concstruction of hotel building. Subject of the solutions is reinforced concrete monolithic point – supported ceiling slab, columns, foundations and staircase. Assesment of these structures by the first ultimate state – carrying capacity.
Load bearing RC structure of hotel building
Keywords: Železobetonová monolitická bodově podepřená konstrukce; nosná konstrukce; železobetonový monolitický sloup; základová patka; základový pás; schodiště; I. mezní stav únosnosti.; Reinforced concrete monolithic point – supported ceiling slab; carryng structure; reinforced concrete monolithic column; foundation block; foundation strip; staircase; first ultimate state – carrying capacity.